Dose-dependent detoxication of the airborne pollutant benzene in a randomized trial of broccoli sprout beverage in Qidong, China. Issue 3 (3rd July 2019) - Chen, Jian-Guo; Johnson, Jamie; Egner, Patricia; Ng, Derek; Zhu, Jian; Wang, Jin-Bing; Xue, Xue-Feng; Sun, Yan; Zhang, Yong-Hui; Lu, Ling-Ling; Chen, Yong-Sheng; Wu, Yan; et al.
ABSTRACT: Background: Airborne pollutants have collectively been classified as a known human carcinogen and, more broadly, affect the health of hundreds of millions of people worldwide. Benzene is a frequent component of air pollution, and strategies to protect individuals against unavoidable exposure to this and other airborne carcinogens could improve the public's health. Earlier clinical trials in Qidong, China, demonstrated efficacy in enhancing the detoxication of benzene using a broccoli sprout beverage. Objectives: A randomized, placebo-controlled, multidose trial of a broccoli sprout beverage was designed to determine the lowest effective concentration that enhances benzene detoxication adjudged by enhanced excretion of the urinary biomarker, S -phenylmercapturic acid (SPMA). Methods: Following informed consent, 170 subjects were randomly assigned in 5 blocks of 34 each to drink either a placebo beverage ( n  = 55) or 1 of 3 graded concentrations of a broccoli sprout beverage [full ( n  = 25), one-half ( n  = 35), and one-fifth ( n  = 55)] for 10 consecutive days. Concentrations of SPMA arising through induced benzene conjugation with glutathione were quantified by MS in sequential 12-h overnight urine collections during the intervention. Results: MS was also used to quantify urinary sulforaphane metabolites in each dosing regimen that resulted in a median 24-h urinary output of 24.6, 10.3, and 4.3 µmol, respectively, confirming a dose-dependent de-escalation of the inducing principle within the beverage. A statistically significant increase in benzene mercapturic acids in urine was found for the high-dose group (+63.2%) during the 10-d period. The one-half dose (+11.3%) and one-fifth dose groups (−6.4%) were not significantly different from placebo controls. Conclusions: An intervention with a broccoli sprout beverage enhanced the detoxication of benzene, an important airborne pollutant, when dosed at a concentration evoking a urinary elimination of ∼25 µmol sulforaphane metabolites per day, and it portends a practical and frugal population-based strategy to attenuate associated long-term health risks of air pollution. This trial was registered at clinicaltrials.gov as NCT02656420.